Multiphase reactions of organic peroxides and nitrite as a source of atmospheric organic nitrates - Yu Yang; Liubin Huang; Min Zhao; Yan Wu; Yihang Xu; Qinyi Li; Wenxing Wang; Likun Xue (Nature Communications)
Abstract Organic nitrates (ONs) are considered as important tracers of secondary organic aerosol formation and are ubiquitous in ambient aerosols. However, the mechanisms of ON formation in the atmosphere are not well understood. Here, we show that ONs can be formed via multiphase reactions of organic peroxides with nitrite. Yields of ONs are measured as 12.8–14.9% at pH 3. The mechanism involves the recombination of a [RO• •NO2] caged radical pair resulting from the homolytic cleavage of alkyl peroxynitrite intermediate. ON yield decreases with the decreasing pH values, which may be ascribed to the positive dependence of its hydrolysis rate on the solution acidity. Additionally, it is found that the second-order rate constant of the reaction is closely dependent on pH and the molecular structure of organic peroxides. Extrapolation of kinetic and mechanistic results to the real atmosphere suggests that this pathway is important for ON formation in aerosols under typical atmospheric conditions, particularly in polluted urban areas.